A descriptive-multivariate analysis of community knowledge, confidence, and trust in COVID-19 clinical trials amongst Ugandans working in healthcare settings. - Keneth Iceland, Kasozi; Lawrence Obado, Osuwat (2021)
Background: Misinformation often undermines community vaccine uptake, yet information in rural communities, especially of developing countries, is scarce. This study was to identify major challenges associated with COVID-19 vaccine clinical trials amongst Ugandans employed in healthcare settings. Methods: A rapid exploratory survey with questions was conducted over 5 weeks at multiple health care centers across the country using an online platform. Questions assessed knowledge, confidence, and trust scores on COVID-19 vaccine clinical trials (KCTCOVacTrials), and the social demographics in the community. Results: A low level on the KCTCOVacTrials was reported amongst healthcare workers in Uganda, thus highlighting challenges for the upcoming Oxford-AstraZeneca clinical trials. Inadequate human resource to handle COVID-19 cases in rural healthcare centers continue to contribute to the mistrust and confidence on COVID-19 clinical trials. In the healthcare centers, a majority of participants were males (171/260, 65.8%, 95% CI: 59.8-71.4), demonstrating disproportionate gender inequalities since most women work in inferior positions which would have made it hard for them to participate in this study. KCTCOVacTrials were higher amongst the least educated (certificate holders) than bachelor degree holders. Skepticism against DNA recombinant vaccines (DRV) implies genetically modified vaccines such as the Oxford- AstraZeneca vaccine, Pfizer/BioNTech are bound to face a level of resistance once adapted in Uganda. This was important since there was a high preference for herbal vaccines, currently being promoted by the government, despite a lack of infrastructure to successful develop a vaccine by any resource poor country in Africa. Furthermore, high fear and distrust against COVID-19 vaccine clinical trials was common in the rich and most affluent regions of Uganda. CONCLUSION: Knowledge, confidence, and trust in COVID-19 vaccines are all low among healthcare workers in Uganda. These findings signal a need to increase these factors before new trials of COVID-19 vaccines are initiated.